Effectiveness Of Financial Reporting On Share Prices In Mining Public Listed Companies On The Indonesian Stock Exchange (IDX) - Taskurun; Muhammad Azis (Universitas Medan Area, 2023)
Financial statement information is one of the important factors in assessing the stock price of a company, many investors before deciding to invest their capital in the company they want to go to first look at financial information, so this study focuses on analyzing the effect of PM, ROA, CR, SR, and PER on the stock price of a coal & lignite mining company on the IDX in 2018-2022. The focus of this study uses three grand theories, namely value theory, market finance theory, and market efficiency theory, each of which explains the effect of financial statement information on stock price fluctuations. The results of the analysis show that PM has a negative and important effect on stock prices, while ROA and PER have a positive and important effect. CR and SR have no significant influence. The coefficient of determination shows that these variables only explain 30% of the influence of stock prices, the rest are influenced by other factors. The implication of this study is that companies need to improve ROA and PER for better stock performance. Limitations of this study include data quality, external factors, and methodology.